2022
DOI: 10.3390/cells11162538
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Regulation of the Insulin-Degrading Enzyme: Role of microRNAs and RBPs

Abstract: The evident implication of the insulin-degrading enzyme (IDE) in Alzheimer’s disease (AD) and type 2 diabetes mellitus (T2DM), among its capacity to degrade insulin and amyloid-β peptide (Aβ), suggests that IDE could be an essential link in the relation between hyperinsulinemia, insulin resistance and AD. However, little is known about the cellular and molecular regulation of IDE expression, and even less has been explored regarding the post-transcriptional regulation of IDE, although it represents a great mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 85 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…This reduction in IDE enzymatic activity would lead to increased levels of insulin interacting with brain regions involved in cognitive function 46,47 . In addition, recent in vitro studies have demonstrated the role of miRNAs and RNA‐binding proteins in IDE regulation 48 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reduction in IDE enzymatic activity would lead to increased levels of insulin interacting with brain regions involved in cognitive function 46,47 . In addition, recent in vitro studies have demonstrated the role of miRNAs and RNA‐binding proteins in IDE regulation 48 …”
Section: Discussionmentioning
confidence: 99%
“… 46 , 47 In addition, recent in vitro studies have demonstrated the role of miRNAs and RNA‐binding proteins in IDE regulation. 48 …”
Section: Discussionmentioning
confidence: 99%
“…It has been also demonstrated that overnutrition-related signals upregulate the expression of Bace1 [39]. Accordingly, IDE can be finely modulated by metabolic stimuli, and it has been proposed as a key molecular link between AD and insulin resistance [40,41]. It has been demonstrated that HFD may induce hippocampal insulin resistance by altering the activation of insulin receptor downstream effectors and transcription factors [27].…”
Section: Discussionmentioning
confidence: 99%
“…These small non-coding RNA molecules bind by complementarity to the 3 0 -UTR of target mRNAs, regulating therefore their expression at posttranscriptional and translational levels and subsequently controlling diverse biological processes, for example, embryonic development, fat storage, insulin secretion, drug metabolism, apoptosis, cell growth and tumorigenesis. [82][83][84][85][86][87] The involvement of liver miRNAs in the regulation of genes expression as a response to dioxin exposure was previous investigated over a restricted scale. [88][89][90] Thus, the current study was conducted to present a wider overview on the transcriptional pattern of miRNAs in the mouse liver after exposure to TCDD to determine the potential regulatory effects these miRNAs on the target mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) gained a considerable attention as effective and determinant suppressors for the expression of target mRNAs. These small non‐coding RNA molecules bind by complementarity to the 3′‐UTR of target mRNAs, regulating therefore their expression at posttranscriptional and translational levels and subsequently controlling diverse biological processes, for example, embryonic development, fat storage, insulin secretion, drug metabolism, apoptosis, cell growth and tumorigenesis 82–87 …”
Section: Introductionmentioning
confidence: 99%